Strengthening the capacity of the National Agricultural Research Systems (NARS) to sustainably manage the outbreak of banana Xanthomonas wilt in East and Central Africa - Karamura, E.B.; Johnson, V. (2012)
Since 2001 banana Xanthomonas wilt has seriously threatened East and Central African food and income security. The paper describes Bioversity’s response in coordinating regional partners to develop a novel communications strategy to raise stakeholder awareness for managing the disease across east Africa. Bioversity engaged multiple stakeholders to develop tools for disease control in a coordinated multi-media communication strategy. Communication materials included a novel blend of: brochures; leaflets; billboards; clothing-slogans; radio talk-shows; drama; training workshops; CDRoms, and posters and videos , as well as a bilingual website. Results showed that around 51,000 farmers in target sites tripled yields, achieving extra income >US$ 67 million. At the sub-regional level, the rate of reported disease outbreaks went down by 20-40%.